2009
DOI: 10.1007/s00244-009-9422-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Dioxin-Like Soil Contamination in Mexico by Enzyme-Linked Immunosorbent Assay

Abstract: In this work, we describe the results of a preliminary soil assessment program for the detection of dioxins at different sites in Mexico performed by immunoassay. We studied five different sectors considered relevant sources of dioxins: Anaversa and Tekchem industrial areas where Correspondence to: E. García-Nieto, mirosgn@yahoo.com.mx. NIH Public Access Author ManuscriptArch Environ Contam Toxicol. Author manuscript; available in PMC 2011 February 3. NIH-PA Author ManuscriptNIH-PA Author Manuscript NIH-PA Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Although the overall dioxin emissions are being reduced in economically developed areas, new sources of emissions are emerging in marginalized countries. A rapidly increasing trend observed in marginalized economies is the use of wood or coal-fuelled stoves to cook and heat houses (Garcia-Nieto et al, 2009). Dioxin has been found as an impurity within PCP treated wood, which is used as a fungicide and herbicide (Vollmuth et al, 1994).…”
Section: Current Detection Methods Utilized In Economically Marginalized Countriesmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the overall dioxin emissions are being reduced in economically developed areas, new sources of emissions are emerging in marginalized countries. A rapidly increasing trend observed in marginalized economies is the use of wood or coal-fuelled stoves to cook and heat houses (Garcia-Nieto et al, 2009). Dioxin has been found as an impurity within PCP treated wood, which is used as a fungicide and herbicide (Vollmuth et al, 1994).…”
Section: Current Detection Methods Utilized In Economically Marginalized Countriesmentioning
confidence: 99%
“…Dioxin has been found as an impurity within PCP treated wood, which is used as a fungicide and herbicide (Vollmuth et al, 1994). This has created a significant new source of dioxins that are emitted, and have left communities highly exposed on an unknowingly and continuous basis (Garcia-Nieto et al, 2009). Several marginalized economies have reported that dioxins and furans are a contaminant in several environmental matrixes including: food (Muntean et al, 2003;Schecter et al, 2003), fly ash (Aristizabal et al, 2008;Wyrzykowska et al, 2009), soil (Minh, et al, 2003;Takazawa et al, 2004;Alawi et al, 1996) and sediment (Tundo et al, 2004).…”
Section: Current Detection Methods Utilized In Economically Marginalized Countriesmentioning
confidence: 99%
See 2 more Smart Citations
“…We have demonstrated these routine immunoanalytical techniques using environmental and biological samples such as house dust, soil, water, urine, and blood. 14,16,17 …”
Section: Introductionmentioning
confidence: 99%